Kontribusi Motivasi Berprestasi terhadap Regulasi Diri Siswa Membolos di Madrasah Aliyah Negeri 2 Payakumbuh serta Implikasinya terhadap Layanan Bimbingan dan Konseling - Suhendra, Marta; S, Neviyarni; Ahmad, Riska (Konselor, 2016)
Abstract Self-regulation is influenced by some factors, like achievement motivation. Studentsâ€™ inability to regulate themselves in learning is reflected through doing truant. This research is aimed at describing: (1) self-regulation of truant student, (2) achievement motivation of truant students, (3) the contribution of achievement motivation toward self-regulation of truant student, (4) the impact of achievement motivation and self-regulation of truant students toward guidance and counseling services. This research used quantitative approach with descriptive and correlation methods.Â  The population of this research was 35 students of class X and XI MAN 2 Payakumbuh. The sample of this research was 35 students using total sampling method, who ever did truant at least 5 times in a semester. The data was collected aquestionnaire and analyzed by using descriptive statistics and analysis of simple linear regression. The finding of this research: (1) the level of achievement motivation of truant students was high, (2) the level of self-regulation of truant students was high, (3) contribution of achievement motivation toward self-regulation of truant students was 34,6% with a significant 0,000. In order to develop self-regulation of the truant students, the guidance and counseling can give counseling service through: (1) information services related to the importance happy to subject teachers and the material presented so that we are not saturated in learning, (2) guidance and group service to the topic of harm ditching task and the importance of learning, (3) mastering content service mastery tips on improving achievement motivation and self-regulation. Theservice programis doingtoincrease of achievementmotivationandself-regulationstudents, so the studentscan do self regulationandachievementin learning.